Evaluation of Clinical Outcomes in Sport Participants Undergoing Anterior Cruciate Ligament Reconstruction - Rawung, Rangga B. V.; Lengkong, Andriessanto C.; Lampus, Harsali F.; Bagy, Raynald G.; Sundah, Antony B. M.; Tooy, Christorei D. (Universitas Sam Ratulangi, 2025)
Anterior cruciate ligament (ACL) injury is one of the most common musculoskeletal injuries. Evaluating the clinical outcomes of the ACL reconstruction (ACLR) procedure is essential to provide information regarding the benefits of this procedure. This study aimed to assess the clinical outcomes of patients who underwent ACLR at Prof. Dr. R. D. Kandou Hospital Manado. This was a retrospective study. Secondary data were collected from all athlete patients who underwent ACLR. The ACLR procedure was performed by a single operator following the standard arthroscopic procedure. All grafts used Hamstring grafts (gracilis and semitendinosus). Suspense fixation was done using a button, while tibial fixation was done with interference fixation (bioabsorbable screw). Patients were evaluated over a short period, specifically at three months, six months, and nine months. Outcome parameters were assessed using the Visual Analog Scale (VAS), Range of Motion (ROM), Lachman test, Anterior Drawer test, and Knee Functional Score (KFS). Any complications that arose were documented. The results showed that among 21 patients at Prof. Dr. R. D. Kandou Hospital Manado, it was found that ACL injuries were more common in physically active men, especially in the age group of 26-30 years. Most patients who underwent ACLR had serious injuries that required immediate treatment. Hamstring graft was the most common choice (85.7%). Knee stiffness was the most common complication and required special attention during the rehabilitation program. Based on KFS, most patients successfully achieved good knee function recovery. There was a decrease in the VAS score reflecting the effectiveness of the procedure in reducing postoperative pain. There was an increase in the KSS reflecting the success of ACLR in restoring knee stability and function to almost normal levels. In conclusion, anterior cruciate ligament reconstruction in sport participants showed significant improvements in knee mobility and pain reduction, with low complications. Keywords: anterior cruciate ligament injury; anterior cruciate ligament reconstruction; graft fixation